PENDAMPINGAN KEGIATAN PENDIRIAN KIOS SEMBAKO UNTUK MENAMBAH PENDAPATAN PKK RT 01/RW 06 KELURAHAN GADING KASRI - Dewi Nurjannah; Sri Nastiti Andarini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The Family Welfare Movement (PKK) group in RT 01/RW 06, Gading Kasri sub-district, which is a partner in this community service, operates a cooperative. Because it is not yet a legal entity, it is actually still a pre-cooperative. All members have shares/principal savings, mandatory savings, and voluntary savings/savings. The "Gading Makmur" cooperative is quite active in PKK members' activities and has capital from principal and mandatory savings. Every holiday, voluntary savings/savings are distributed, along with additional SHU (Surplus Operating Income) from member savings and loans, whose services will be distributed to PKK members who have already joined the cooperative. The PKK cooperative has not been able to expand its business to increase PKK income. Therefore, there is a plan to open a grocery kiosk with the consideration of obtaining additional PKK income in addition to the savings and loans that have been running well so far. There is no need to open a large grocery store, but rather adjust to existing capital. However, limited human resources are a constraint, because the kiosk manager must be a PKK member who is trustworthy and has a strong social spirit, including a lack of knowledge about fund management and distribution plans. Based on these issues, our team's community service activities include assisting with planning the establishment of a grocery kiosk, providing training in business financial management and developing a plan for the distribution of the SHU (profit sharing) and providing guidance on opening a grocery kiosk and maintaining its financial records.